2020
DOI: 10.1002/jsfa.10810
|View full text |Cite
|
Sign up to set email alerts
|

Calcium applications throughout fruit development enhance olive quality, oil yield, and antioxidant compounds' content

Abstract: BACKGROUND Calcium is a preservative and firming agent largely used in the table olive industry. Foliar applications of calcium (as calcium chloride, CaCl2) before harvest have been proposed in other fruits to increase firmness and reduce physiological disorders or internal damage. However, there is still a shortage of information regarding the source, the concentration, the number, and the period of calcium application onto the canopy to get an effective response of olive quality. In this study, we aimed to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…Moreover, neochlorogenic and cryptochlorogenic acids increased after the application of organic Ca, while the accumulation of chlorogenic acid was enhanced by CaCl 2 . In a previous study, CaCl 2 foliar application increased the phenolic content of olive fruit [40]. In our study, higher values of individual phenolics were usually found in the fruit from Agios Vlasios orchard.…”
Section: Total Antioxidant Activity Total and Individual Phenolic Con...supporting
confidence: 71%
“…Moreover, neochlorogenic and cryptochlorogenic acids increased after the application of organic Ca, while the accumulation of chlorogenic acid was enhanced by CaCl 2 . In a previous study, CaCl 2 foliar application increased the phenolic content of olive fruit [40]. In our study, higher values of individual phenolics were usually found in the fruit from Agios Vlasios orchard.…”
Section: Total Antioxidant Activity Total and Individual Phenolic Con...supporting
confidence: 71%
“…Tsantili et al (2008) reported that calcium chloride spray three applications before harvested increased pulp of black-ripe 'Konservolia' olive. Morales-Sillero et al (2020) confirmed that calcium foliar sprays before harvest increased pulp oil content (dry weight basis), in addition to reduction of physiological disorders of green table olives.…”
Section: Introductionsupporting
confidence: 53%
“…For K and P, higher mean levels were found in organically compared to conventionally produced olives (763 to 212 mg kg −1 and 101 to 55.4 mg kg −1 , respectively) ( Table S3–S5 ). The 3-fold higher Ca levels in conventionally produced olives might be attributed to the application of calcium chloride as a food additive during fruit development and packaging to improve fruit quality and to increase preservability and texture ( Morales-Sillero et al, 2021 ). In contrast, 3.6 to 1.8-fold higher levels of K and P were found in organically compared to conventionally produced olives, respectively ( Table S4 and S5 ).…”
Section: Resultsmentioning
confidence: 99%